(untitled) (Research, Society and Development, 2021)
This article aims to show people management as an important tool for the success of an event such as a wedding, the necessary mechanisms will be shown for such a celebration to occur satisfactorily, from planning to execution, with the main link to the Assessoria de marriage for the perfect conduct of the solemnity. Allied to statistical data and step by step for the event, such as the combination of quality and satisfaction, showing resources, actions and studies. With an emphasis on preparing the people who make the event happen, knowing how to deal with unforeseen events, bypassing them or making possible adaptations, in a way that is imperceptible to the eyes of customers and guests, thus contributing to the success of the festival. It was found through research that the number of weddings and parties reduced, due to external factors, even couples who were already planning had their dreams postponed, demanding that the care with the provision of services be even greater, as they are dealing with feelings, dreams and anxiety. Prior knowledge in administration will be necessary for the company’s progress, within that leadership and marketing will be essential, always prioritizing ethics and transparency.